2020
DOI: 10.1080/10942912.2020.1807565
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant and anti-aging properties of swim bladder peptides from Atlantic cod (Gadus morhua)

Abstract: Two bioactive peptide fractions (SWP-I and SWP-II) of swim bladder peptides from Atlantic cod (Gadus morhua) were obtained through enzymatic hydrolysis and isolated by gel filtration chromatography. The properties of two fractions were characterized by FT-IR, UV scanning spectroscopy, amino acid composition analysis and molecular weight determination. The results showed that the content of aromatic amino acids in SWP-II was higher than that in SWP-I, and the molecular of SWP-I and SWP-II were 4976 Da and 1960 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Collagen yield varies from 30 to 60% based on the species and methods of isolation [ 31 , 70 , 71 ]. Owing to the presence of specific peptides and amino acids, fish collagen hydrolysates have pharmacological benefits, such as anti-inflammatory, antibacterial, antitumor, antiaging, and free radical scavenging activities [ 72 , 73 ].…”
Section: Structures and Compositions Of The Swim Bladdermentioning
confidence: 99%
“…Collagen yield varies from 30 to 60% based on the species and methods of isolation [ 31 , 70 , 71 ]. Owing to the presence of specific peptides and amino acids, fish collagen hydrolysates have pharmacological benefits, such as anti-inflammatory, antibacterial, antitumor, antiaging, and free radical scavenging activities [ 72 , 73 ].…”
Section: Structures and Compositions Of The Swim Bladdermentioning
confidence: 99%
“…The results showed that CSSPs played an anti-oxidant and anti-aging role [ 48 ]. Moreover, two bioactive peptide fractions (SWP-I and SWP-II) from the swim bladder of Atlantic cod (Gadus morhua) were isolated and pretreated with SWP-I and SWP-II on prematurely senescent 2BS cells induced by hydrogen peroxide (H 2 O 2 ), and it was found that SWP-I and SWP-II could effectively scavenge DPPH-, HO - , and O 2− ; improve Fe 2+ chelating activity; increase cell survival; and inhibit SA-β-gal activity and apoptosis rate, indicating that they are peptides with both anti-oxidant and anti-aging properties [ 49 ]. There are also studies on grass carp (Ctenopharyngodon idella) skin, where three novel peptides (PTSPL/GPGPGL/VGGAP) with known sequences derived from the proteolytic digest of grass carp skin have potent anti-oxidant activities, and although their potential health benefits need to be explored through simulated digestion and animal studies, the powerful anti-oxidant activities shown in the current study and the findings provide evidence that these three anti-oxidant peptides are useful in delaying aging or extending the life of cells.…”
Section: Marine Peptides That Intervene In the Aging Processmentioning
confidence: 99%
“…The absorbance was detected at 280 nm. According to the elution curve, the main fractions were collected as AKP (Li et al, 2020).…”
Section: Preparation Of Antarctic Krill Peptidementioning
confidence: 99%
“…can react with almost every biological molecule found in living cells and cause tissue damage through oxidizing proteins, carbohydrates, nucleic acids and lipids. DPPH• is another strong reactive free radical which is stable in ethanolic solutions and has a maximum absorbance at 517 nm because of its odd electron ion (Li et al, 2020).…”
Section: Attenuation Of H 2 O 2 -Induced Oxidative Stress In Mc3t3-e1 Cellsmentioning
confidence: 99%